An unusual thermal oxidation of triaryloxazoles. Issue 23 (3rd June 2015) - Pickett, James E.
Graphical abstract: Abstract: Triaryloxazoles undergo slow but smooth thermal oxidation at 135–175 °C to produce nitrile and anhydride products apparently arising from endoperoxides formed from the addition of oxygen to the heterocyclic ring. The Hammett ρ value of ca. −0.7 and activation energy of ca. 87 kJ/mol (21 kcal/mol) seemed to rule out an electron-transfer mechanism. A mechanism involving a peroxidic biradical and a triplet to singlet spin flip is suggested.